Komunikasi Krisis Terkait Asumsi Krisis Etika Pemilihan Presiden RI pada Putusan Mahkamah Konstitusi Tahun 2024 - Faustyna, Faustyna (Mahesa Research Center, 2024)
This study aims to analyze crisis communication related to the assumption of ethical crisis in the presidential election of the Republic of Indonesia developed and implemented, including communication strategies used by various related parties. How crisis communication is related to the assumption of an ethical crisis in the presidential election of the Republic of Indonesia developed throughout the period. Qualitative methods with content analysis to understand crisis communication and ethical issues and explored related parties involved in the presidential election process, including presidential candidates, political parties, and governments, responding to and managing such situations through crisis communication. The study's findings provide a deep understanding of crisis communication that can affect public perceptions and beliefs as well as the integrity of the presidential election process and Constitutional Court decisions, from reactive to proactive. The dominant pattern involves rhetoric to defuse tensions, clarify misinformation, and reinforce a positive image. To improve the effectiveness of crisis communication, they should adopt a proactive approach in crisis communication by conducting periodic risk analyses and developing comprehensive contingency plans. Effective rhetoric to ease tension, clarify misinformation, and reinforce a positive image. Training and crisis simulation for communication teams are also indispensable.